The modification, translation, and validation of the Malaysian version of Score for Allergic Rhinitis (SFAR) questionnaire - Siew Chung Cheah; Aneeza Khairiyah Wan Hamizan; Farah Dayana Zahedi; Marina Mat Baki; Salina Husain (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background Score for Allergic Rhinitis (SFAR) is a validated self-administered questionnaire to assess for allergic rhinitis (AR) in a population setting but was designed for a temperate climate. Objective This study aims to modify the SFAR for the tropical climate, translate the modified SFAR from English to Malay Language, and validate this Malaysian version of SFAR (MySFAR). Methods This was a cross-sectional study at an outpatient Otorhinolaryngology clinic in a tertiary center. There were 2 phases in the study: (1) the translation and validation of SFAR and (2) the testing of diagnostic accuracy. Two different groups of participants were recruited for the respective phase. Results In phase 1, the total MySFAR score showed good discriminant validity between AR and healthy controls (13.44 ± 1.58 v 1.00 ± 2.12, p < 0.01). The internal consistency and test–retest reliability of MySFAR was excellent with Cronbach’s alpha 0.92 (95% CI 0.90–0.94) and intraclass correlation coefficient of 0.97, p < 0.01. In phase 2, MySFAR gave an AUC of 0.98 (95% CI = 0.96–1.00, p < 0.01), and a cut-off score of > 9 (J = 0.92) was determined based on the highest Youden index. This cut-off was 97.8% sensitive and 93.9% specific to predicting allergic rhinitis from non-allergic rhinitis. Conclusion The present study showed good validity and reliability of MySFAR among the Malaysian population. The cut-off score of > 9 was able to predict allergic rhinitis. This would be a useful screening tool for allergic rhinitis population studies in tropical countries.